POSTCOLONIAL LITERATURE IN ENGLISH TO IGNITE A BRIGHTER FUTURE OF EFL IN MULTILINGUAL SOCIETIES - Delvi Wahyuni (Universitas Negeri Padang, 2016)
English is now spoken by more non-native speakers (NNS) than by native speakers (NS) due its global outreach. There are some implications emanating from the conditions mentioned above. First, the notion of the language ownership is being contested. There is a strong demand to the recognition of varieties of English emanating from countries of Kachru’s outer and expanding circles. Second, this Yuing demography of the speakers of English has rendered those who use it as their vernacular as the minority. Interestingly, it does not make the notion of native-speakerism, by which native speaker’s norms and standards should be set as a benchmark for a success in learning the language, recedes in ELT. In multilingual societies where English is a foreign language (Indonesia will be a very good example), ELT is very challenging due to the language not being used for day-to-day communication, and the interference of the learners’ L1 and L2 to their English. As a result, the English which they produce might not comply with the standard norms. To deal with that problem, there have been efforts to interrogate the validity of native speakerim in ELT in countries like Indonesia due to the increasing awareness that the goal of the teaching of English in this region is to use the language successfully in various communication settings thus native-like proficiency is less relevant. For that reason, this paper suggests the introduction Postcolonial Literatature in EFL syllabus to afford learners new insights on the language and hence building their confidence and therefore competence in the language.